Halal knowledge grid model for promoting knowledge sharing among their community of practice - Abdullah, Rusli (2014)
The power of knowledge management (KM) as a system in capturing, storing, disseminating, and use knowledge for the benefits of its community of practice (CoP) can’t be debated anymore especially in promoting knowledge sharing among them. While, Halal is an industry that was identified as a process that can be provided a lot of content into the KM system by the CoP whether directly or indirectly where they are scatted around the particular states or countries for their future references. The combination of KM and Halal is becoming important in producing and delivering a halal knowledge grid (Halal K-Grid) especially in Malaysia context locally and internationally in order to link and synergies the halal industries which is starting from the beginning of its happening of halal industries inclusive the manufacturing, marketing, as well as its application to the end users. Therefore, there is a need of a special mechanism in terms of or model framework, on how to ontology and in manipulating the halal knowledge semantically and connectively as a halal knowledge grid towards quality of services (QoS) in terms of its usability, accessibility, reliability, and security to its CoP at anywhere, anytime and any platform whether through desktop or mobile computing.